Effect of sitagliptin on depression in male wistar rats - Mahalmani, Vidya M.; Hogade, Anil P.; Mishra, Sanjay K. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Growing evidence supports relationship between depression and inflammation. The hypothesis of involvement of inflammatory pathways in depression is supported by the findings of increased levels of proinflammatory cytokines. So, we decided to evaluate the effect of sitagliptin on depression using forced swim test (FST) and possible effects of sitagliptin on serum oxidative stress markers and cytokine gene expression in rat hippocampus. Methods: FST model was used to evaluate antidepressant effect in male wistar rats. Rats in group I (control group) were given normal saline, group II (standard group) were given fluoxetine, group III and IV (test groups) were given sitagliptin 5 mg/kg and sitagliptin 9 mg/kg respectively. All the drugs in all groups were given per orally. At the end, animals were sacrificed and blood was collected. Hippocampus of rat brain was dissected out. Serum oxidative stress markers and hippocampal pro inflammatory cytokine gene expression analysis was carried out. Results: Sitagliptin 5 mg/kg and 9 mg/kg showed reduction in depressive symptoms and hippocampal cytokine gene expression in comparison to control. In case of serum oxidative stress markers, there was statistically significant reduction in nitric oxide levels with stagliptin 9 mg/kg. Although there was a decrease in the levels of catalase and increase in the levels of glutathione with standard and test groups, the results were not statistically significant. Conclusions: The present study showed significant antidepressant effect activity of standard and test groups. Hence, further research should be carried out to substantiate above results.